Nonassociation of Paleoindians with AMS-Dated Late Pleistocene Mammals from the Dutchess Quarry Caves, New York - D. W. Steadman; T. W. Stafford Jr.; Funk, R. E. (Quaternary Research, 1997)
AMS14C ages of 10 bones of the caribou (Rangifer tarandus), flat-headed peccary (Platygonus compressus), and giant beaver (Castoroides ohioensis) from the Dutchess Quarry Caves, New York, range from 13,840 ± 80 to 11,670 ± 70 yr B.P. No bones from any of these species are demonstrably associated with Paleoindian artifacts (fluted points) or other cultural materials from the sites because the bones lack unequivocal stratigraphic association with artifacts, as well as physical (taphonomic) evidence for human association (e.g., burning, cut marks, distinctive breakage). Together with the Holocene conventional14C dates of charcoal and the varied stratigraphic proveniences of the fluted points and the dated bones, the new AMS14C dates argue that most strata at the Dutchess Quarry Caves contain a mixture of late Pleistocene and Holocene materials. This mixing probably resulted from post-depositional bioturbation (by humans, rodents, carnivores, and scavengers) and cryoturbation (annual freeze–thaw cycles). Rather than being of cultural origin, the bones of caribou, flat-headed peccary, and giant beaver likely were deposited in the Dutchess Quarry Caves by nonhuman predators or scavengers, such as ursids, canids, felids, condors, or eagles.
Keywords: AMS dating; caribou; Castoroides ohioensis; Dutchess Quarry Caves; flat-headed peccary; giant beaver; New York; Platygonus compressus; Rangifer tarandus